Approaches for estimating the unsaturated hydraulic conductivity of compacted quartz sand via particle packing theory - Qiang Liu; Liang Guo; Jiali Miao; Xiangchao Qu; Shujie Xiao (Scientific Reports)
Abstract The unsaturated hydraulic conductivity (K) is one of the most important properties for evaluating moisture and gas migration in soil. However, the precise measurement of K in the laboratory often requires considerable time and economic costs. Currently, the most commonly used method to calculate K is to obtain it from the soil–water characteristic curve (SWCC) and saturated hydraulic conductivity. The void ratio e has a crucial influence on the variation in K. In this study, by combining two extended SWCC models (the Kwan model and the modified linear packing density model (MLPDM)) proposed by Liu et al. and two models (Model K S1 and Model K S2) for predicting the saturated hydraulic conductivity (K S ) of compacted quartz sand, two approaches (Approach I and Approach II) for estimating the K of compacted quartz sand were proposed. A series of laboratory experiments (constant head permeability tests and alternative simplified evaporation tests) were conducted to verify and evaluate the accuracy and applicability of the two approaches for predicting the K values of compacted quartz sand. For Approach I, the average RMSE was 6.31 × 10− 6. For Approach II, the average RMSE was 5.82 × 10−6. Both Approach I and Approach II provided accurate and reasonable K values for 20 compacted quartz sand samples. Therefore, Approach I and Approach II can be used to predict moisture and gas migration in compacted quartz sand.